Peningkatan Kreativitas dan Inovasi Produk Olahan Ikan Sebagai Penggerak Ekonomi Lokal di Desa Lubuk Tukko - Putri Anggraini; Dinda Aulia Sari; Putri Hayati; Nur Aisyah Tanjung; Mhd Yadi Harahap (Lembaga Pengembangan Kinerja Dosen, 2026)
This article examines the role of creativity and innovation in the development of processed fish products as a driver of local economic growth in Lubuk Tukko Village. Through the Community Service Program (KKN), training and mentoring were provided to MSMEs in product diversification, quality improvement, and digital marketing. The results showed increased product added value, market expansion, and the growth of entrepreneurship among the village community. Innovation in processed fish products not only increased household income but also created new jobs and strengthened village food security. The main obstacles faced included limited capital and technology, which could be overcome through cross-sectoral collaboration. This program serves as a model for economic empowerment based on local resources that is adaptive, innovative, and sustainable.